Pengaruh Pemanfaatan Teknologi Informasi (TI), Sistem Pengendalian Internal (SPI), dan Penerapan Sistem Informasi Akuntansi (SIA) Terhadap Kualitas Laporan Keuangan Lembaga Perkreditan Desa (LPD) - Sujatmika, Dewa Made Dwi; Kresnandra, Anak Agung Ngurah Agung (Ekonomis: Journal of Economics and Business, 2026)
The purpose of this study is to obtain empirical evidence regarding the influence of information technology utilization, internal control systems, and the implementation of accounting information systems on the quality of financial reports at the Village Credit Institution in Klungkung Regency. The sampling method used was non-probability sampling with purposive sampling. The number of samples used was 85 samples obtained from the Slovin formula, namely LPD employee respondents selected according to certain criteria. Data collection was carried out using a questionnaire. The collected data were then analyzed using multiple linear regression analysis techniques. The results of this study concluded that simultaneously and partially there was a positive and significant influence between the variables of information technology utilization, internal control systems, and the implementation of accounting information systems on the quality of financial reports at the LPD in Klungkung Regency.